Variações da comunidade fitoplanctônica na região estuarina dos rios Piraquê-Açú e Piraquê-Miriam (Aracruz, ES) e suas relações com os fatores ambientais - Schaeffer, Jane Karla (2005)
This study was carried out in the estuary of the Piraquê- Açú and Piraquê-Mirim rivers, located in the municipal district of Aracruz-ES (Brazil). The aim of this study is to verify both spatial and temporal changes on phytoplanktonic community of the estuary in its qualitative and quantitative aspects, and also to evaluate the biomass through the technique of biovolume. Moreover, the obtained biotics variables were related with abiotic variables analized at the same spots along the estuary. The obtained results were based on samplings carried out bimonthly in the period of August 2003 to February 2004, emphasizing two pluviometric seasons: dry (August) and rainy (February). Pheopigments concentrations were higher than chlorophyll a concentration, showing a senescent degree of the community. The qualitative aspect of the phytoplankton community showed 156 taxons classified in species, genus and varieties, wich most of them considered as marine, eurialine and planktonic. The dominant classes were Bacillariophyceae (57%), Chlorophyceae (11,5%) and Dinophyceae (8,4%). Although, the community showed a higher diversity, just some were quantitatively significant, among them Cyanophyceae Synechocystis aquatilis, Chlorophyceae Chlorella minutissima and Bacillariophyceae Melosira varians. The highest densities of total phytoplankton occured in the rainy season. Such variations were related to a significant contribution of allochthonous nutrients and materials originated from superficial outflow during the rainy season. Regarding the biovolume, seven classes of algae showed significative contribution: Chlorophyceae, Bacillariophyceae, Cyanophyceae, Dinophyceae, Cryptophyceae, Euglenophyceae and the phytoflagellates. The most significant contribution for total biovolume was given by Bacillariophyceae and Dinophyceae. Pluviosity was the major external driving force leading to changes in phytoplankton community